Spartanburg Technical College 1998 High School Survey - Quinley, John W.; Cantrell, Jo Ellen; Spartanburg Technical Coll., SC. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This study reports the findings of a high school student survey conducted by Spartanburg Technical College (STC) in South Carolina to determine its service area's needs. Respondents to the survey included 1,501 juniors from 14 high schools in Cherokee, Union, and Spartanburg counties. Students were queried as to what type of college they would consider attending, parental attitudes about college, influences on their decision to pursue postsecondary education, what type of assistance they might need in college, factors deemed important to college choice, and other specifics such as computer skills and preferred instructional delivery methods. Since the study was especially concerned with respondents who might attend STC, the number and percent of respondent 11th graders indicating an interest in STC were analyzed by high school, ethnicity, and gender. Among the results were: (1) fifty-two percent of respondents' parents encouraged them to pursue higher education; (2) financial aid was the most requested service from a future college at 38 percent, with aid in study skills following closely behind at 28 percent; (3) in total, 433 respondents would consider attending STC; and (4) the percentage of whites and blacks who would consider attending STC was identical at 30 percent. (Contains seven graphs.) (EMH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Bound Students; College Choice; Decision Making; High School Students; High Schools; Parent Attitudes; School Community Relationship; Student Attitudes; Student Characteristics; Student Educational Objectives; Student Financial Aid; Student Needs; Surveys; Technical Institutes; Two Year colleges; Spartanburg Technical College SC; Reports, Research